CHANGES IN SCHOOL EDUCATION AND NATIONAL EDUCATION POLICY 2020 - Mishra, Poonam; Mathur, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since independence, there has been a great change and development in all aspects of Indian education. Changes were made in the Indian education system to strengthen the path of national development in accordance with the needs of the individual and society. The role of school education is very important for the overall development of students. The main objective of this study is to discuss the school education of the recently adopted National Education Policy 2020 in the light of the school education of various education commissions and national education policies after independence in India. The data used in this study has been taken from the reports of the above-mentioned commissions and policies. Apart from these, a lot of information has been taken from published journals, articles, dissertations and research works. Content analysis has been used to conduct this study. All the data has been taken from secondary sources. The findings of this study show that the school education system recently adopted in NEP 2020 is an appropriate example of a modern education system, which is more technology and vocational oriented. Multidisciplinary education, vocational education, mother tongue have been given special importance in school education of NEP 2020. All commissions and educational policies have given importance to quality improvement in school education.